DYNAMICS OF GEN Z POLITICAL PREFERENCES: THE ROLE OF E-WOM, DIGITAL POLITICAL ENGAGEMENT, AND POLITICAL LITERACY IN EAST KALIMANTAN - Moh. Reza Munandar; Saida Zainurossalamia; Heni Rahayu Rahmawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study investigates the mechanism underlying the formation of political preferences among Generation Z in East Kalimantan within an increasingly digital political environment. The transformation toward platform-based political communication has intensified the role of user-generated information and online interaction in shaping political orientation. This research aims to examine the effects of electronic word of mouth (e-WOM) and digital political engagement on political preferences, while positioning political literacy as a moderating variable that conditions these relationships. A quantitative approach was employed using survey data collected from Generation Z respondents in East Kalimantan. The analysis applied Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both direct and moderating effects among variables. The findings indicate that e-WOM and digital political engagement significantly influence the formation of political preferences. Furthermore, political literacy plays a critical moderating role in determining how digital political exposure is translated into stable political orientation. These results demonstrate that political preference formation among Gen Z is not solely driven by exposure to digital information, but also by the individual’s ability to critically evaluate political content. By integrating social influence, digital engagement, and cognitive filtering mechanisms, this study offers a more comprehensive model of political preference formation in the digital era, particularly within a non-metropolitan regional context. The findings also provide practical insights for developing more effective and responsible digital political communication strategies targeting young voters.